Change in the volume of water crystallization as a result of exposure to a high-frequency electromagnetic field - Shipunov, B.P.; Zakharova, M.V. (KU Publ., 2021)
The influence of a high-frequency electromagnetic field on the process of water crystallization has been studied. Water irradiated by а field at 30–200 MHz was kept from 0 to 21 days, then it was frozen. Volumes of ice at crystallization were compared for water irradiated and unirradiated by the field. Values located more or less symmetrically near zero; 2) values with a predominantly positive shift, and 3) values for which the shift is mostly negative. Positive shift was noted when combining 200 MHz and the exposure time up to 11 days. The maximum effect of relative volume increase almost two times was observed at 200 MHz and one day exposure time. The maximum compression of ice approximately three times compared to the unirradiated sample occurred twice: after field effect at 90 MHz and exposure time of 11 days, and at 140 MHz and exposure time of 21 days. The similarity of time dependence at 170 MHz with the dependence of thermal effect of glucose dissolution found in early works was noted. The data obtained confirm that field effect results in both strengthening and loosening of water structure.
Жоғарыжиілікті электромагниттік өрістің әсерінен судың кристалдану көлемінің өзгеруі
Изменение объёма кристаллизации воды в результате воздействия высокочастотного электромагнитного поля
Keywords: electromagnetic field; water structure; ice structure; defects in ice structure; frequency of field effect; post-effect changes in water structure; loosening of water structure; strengthening of water structure